Determinants of diffusion and adoption of improved technology for rice parboiling in Benin - Dandedjrohoun, L.; Diagne, A.; Biaou, G.; N'cho, S.; Midingoyi, S.K. (2012)
The widespread use of traditional rice-parboiling methods in Benin leads to poor quality of final rice. To address this problem, the national agricultural research institute of Benin and Africa Rice Center have developed improved rice parboiling technology. An educational video developed by AfricaRice was used for it diffusion. Women have expressed high interest in the use of the technology and have reported that it helps increase the quality of their final rice despite its' relatively high cost. This paper uses the Average Treatment Effect (ATE) framework and data collected from 200 women rice parboilers in central Benin to estimate the actual and potential adoption rates of this technology and the determinants of its diffusion and adoption. 85% of the sampled women were exposed to the technology in 2008. With this incomplete diffusion, the actual adoption rate is 67%, whereas the potential adoption rate is estimated to be 75%. "Being member of a parboilers association'' and "Participation in video training" are positively associated with knowledge and adoption of this technology. This indicates that support and promotion of women parboilers associations is a means to increase technology uptake and access and video-supported training is an extension tool to promote agricultural technology awareness and adoption.